Cost effective direct-substrate jet impingement cooling concept for power application - Mouawad, Bassem; Abebe, Robert; Skuriat, Robert; Li, Jianfeng; De Lillo, Liliana; Empringham, Lee; Johnson, C. Mark; Roberts, Andy; Clarke, Robert; Haynes, Geoff (2018)
Direct substrate jet impingement cooling can eliminate the use of the baseplate and significantly reduce the weight and volume of conventional thermal management solutions. This work demonstrates a cost-effective manufacturing approach based on printed circuit board technology to create impingement cells under a direct bonded copper substrate. Results from both computational fluid dynamics simulations and transient thermal tests verify the good performance of such jet impingement cooling systems under high power density conditions. Further work is ongoing to apply the present cooling and manufacturing technologies for the development of a range of high performance power electronic systems.